Habilidades de conciencia fonológica en estudiantes de primer grado de instituciones educativas públicas de Bellavista - Aguilar Ávalos, Julián (2012)
This descriptive simple research aimed to determine the development of phonological awareness abilities of 232 grader primary students of 6 public schools in Bellavista. The metalinguistic ability test proposed by Gomez, Valero, Buades and Perez, an adapted to our reality by Panca (2003) was used. The results showed that just 48, 7% of the sample reached an advanced level in the development of phonological awareness activities, while 51,3% were below the intended level. We can conclude that there are significant differences in the achievement of the subtests to isolate, count and combine phonemes, which are part of the phonemic awareness, as well as the most complex level of phonological awareness regarding reading.